Intelligent Web-Based Virtual Assistant for Klabat University Using Retrieval-Augmented Generation (RAG) and Text-to-Speech (TTS) Integrated with Large Language Models - Taju, Semmy Wellem; Sandag , Green Arther; Corinta, Ogi Wemy; Mokodompit, Rahayu; Sakka, Mercy Yuliana (12th International Scholars Conference 2025, 2026)
The development of information technology has brought significant changes in the world of education, including at Klabat University. To increase accessibility and ease of obtaining information, a web-based virtual assistant system was developed that utilizes Retrieval-Augmented Generation (RAG) and Text-to-Speech (TTS) technologies. This research aims to implement RAG and TTS technology in a virtual assistant system in order to provide faster and more interactive answers to users. With this system, users can get information faster. The methodology used is Extreme Programming (XP), with an iterative approach in software development. The development process includes planning, design, coding, testing, and continuous feature enhancement. The results showed that the implementation of RAG and TTS improved efficiency in information delivery. Users can ask questions and receive answers in the form of text and voice, making information search more interactive. This system is expected to be an innovative solution for information services at Klabat University and can continue to be developed in the future.